Students' Perceptions towards Learning English on Earthquake Mitigation Education through Animation Video - Natalia Manuhutu; Felisitas Kirikirop Ulian (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2020)
This study purposed to improve students' soft skills, knowledge and interest in learning English through animation videos of earthquake mitigation learning. Then the significances of this study were to improve learning interest-based on students' skill in organizing material and method into the game gradually by manipulating causes of earthquake, picture, and object into the text. The methods used in this research is a combination of conventional lecturing and games; also, several selected animation videos about earthquake mitigation. The sample of this research is 45 students who come from several tribes in Papua, but they study and live together at the boarding school in SMTK GGRIP Merauke. The result of this research was most of the students have good ability in catching the material of learning fast and proactive also, good intention to participate in learning English actively by simulating causes of the earthquake, picture, and object into a text. They were confident to answer quiz both individual or in a group session. It can be concluded that the students can improve their skills, especially for English and teacher can use this alternative model to encourage students in learning English through many things around them in Papua.